Depressed in vitro and in vivo antibody response and adoptive transfer of delayed hypersensitivity to myoglobin with spleen cells of mice chronically infected with Schistosoma japonicum and injected with myoglobin. - Garb, K S (1984)
Spleen cells from C57BL/6J mice infected for 21 weeks with Schistosoma japonicum did not show an in vitro secondary antibody response upon challenge with sperm whale myoglobin. Mice infected for 13 weeks showed almost no in vivo secondary antibody response to this antigen. Spleen cells from mice infected for 12 to 21 weeks did not adoptively transfer delayed hypersensitivity to this antigen.